97.1k views
5 votes
What is x^3−x^2−x+1 divided by x^2−2x+1 ?

User Aymeric
by
5.7k points

2 Answers

6 votes
x^3-x^2-x+1 divided by x^2-2x+1 equals x + 1
User Paebbels
by
5.8k points
2 votes


\displaystyle\bf\\x^3-x^2-x+1 = \\\\=x^2(x - 1) - (x - 1)= \\\\=(x - 1)(x^2 - 1) =\\\\= (x - 1)(x - 1)(x + 1) = \\\\=(x - 1)^2(x + 1) = \\\\(x^2 - 2x + 1)(x + 1)\\\cdots\cdots\cdots\cdots\cdots\cdots\cdots\cdots\\(x^2 - 2x + 1)(x + 1)~\vdots~(x^2 - 2x + 1)\\\\\implies~~x^3-x^2-x+1~~\text{ is divisible by }~~ x^2-2x+1 \\\\Verify:\\\\(x^3-x^2-x+1)/(x^2-2x+1)=((x^2 - 2x + 1)(x + 1))/(x^2-2x+1)=x+1



User Harmstyler
by
5.6k points